Pengaruh PER, ROA, DAR, TATO Terhadap Nilai Perusahaan Pada Indeks SRI-KEHATI - Kenrio Richs; Idham Cholid (MDP Student Conference, 2026)
This study aims to determine the effect of Price to Earning Ratio (PER), Return on Asset (ROA), Debt to Asset Ratio (DAR), and Total Asset Turnover (TATO) on company value in the Sri-Kehati Index for the period 2018–2024. The research method used in this study is quantitative research. The population in this study consists of all companies listed on the Sri-Kehati Index for the period 2018–2024. The research sample was obtained using purposive sampling, consisting of 10 companies. The data analysis technique used was multiple linear regression. The results showed that the Price to Earnings Ratio (PER) had a positive effect on company value, Return on Assets (ROA) had a positive effect on company value, Debt to Asset Ratio (DAR) had a positive effect on company value, and Total Asset Turnover (TATO) had a negative effect on company value.